2020
DOI: 10.1111/codi.14969
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of extended radical resections for locally advanced and recurrent pelvic malignancy involving the aortoiliac axis

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Historically, the presence of hydronephrosis, gross lower limb oedema, and invasion of the sciatic notch or involvement of the aortoiliac axis suggested inoperable disease. Various studies have demonstrated the safety and efficacy of major extra-anatomic resections involving these structures in selective patients [ 64 , 65 , 66 ]. En bloc sciatic nerve and/or lumbosacral trunk resections for tumours extending laterally into the piriformis muscle have demonstrated similar R0 rates to central pelvic tumours [ 13 ].…”
Section: Contemporary Management Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Historically, the presence of hydronephrosis, gross lower limb oedema, and invasion of the sciatic notch or involvement of the aortoiliac axis suggested inoperable disease. Various studies have demonstrated the safety and efficacy of major extra-anatomic resections involving these structures in selective patients [ 64 , 65 , 66 ]. En bloc sciatic nerve and/or lumbosacral trunk resections for tumours extending laterally into the piriformis muscle have demonstrated similar R0 rates to central pelvic tumours [ 13 ].…”
Section: Contemporary Management Strategiesmentioning
confidence: 99%
“…Functional outcomes are always a concern when undertaking these radical resections; however, almost all patients undergoing complete sciatic nerve resection regain mobility post-operatively following intensive physiotherapy and orthotics input [ 64 ]. En bloc major vascular resections of the aortoiliac axis are also shown to be feasible in select patients in specialised centres, with an R0 rate of 81.8% reported in one study [ 65 ].…”
Section: Contemporary Management Strategiesmentioning
confidence: 99%
See 2 more Smart Citations